The Portrayal of Women’s Power Ambivalence: in Literature- to- Film Adaptation of Enola Holmes - Bintang Priyanto Putri; Fatma Hetami; Rahayu Puji Haryanti; Widhiyanto Widhiyanto (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
The pursuit of dreams by women often results in a complex state of ambivalence, as they contend with societal, familial, and personal obstacles. This underscores the need for a new cultural narrative that reconciles the strengths and weaknesses of women. Our research focuses on examining the portrayal of woman's power in the novel and film Enola Holmes. Utilizing a qualitative approach and Betty Friedan's liberal feminism as a framework, we explore the multifaceted nature of female empowerment as represented by the character Enola Holmes. Our findings reveal that Enola's aspiration to become a detective symbolizes female empowerment but is marked by ambivalence. A form of ambivalence can be seen when Enola ends up in boarding school, falls in love with a man, gets help from male friend, gets a culture shock, and uses the name “Holmes”; Eudoria’s absence after her enthusiastic efforts of teaching Enola and making a plan for reform bill with her feminist movement; Dowager's plan to kill Tewkesbury is defeated by Enola Holmes and Tewkesbury; women oppressing women through the character Enola Holmes fights Edith and Enola Holmes argues Miss Harrison. Therefore, these complexities suggest a paradox: efforts to challenge patriarchal norms can inadvertently reinforce the culture they seek to change. In conclusion, our study highlights the nuanced nature of female empowerment in